Bambusa vulgaris leaf area estimation on short-rotation coppice - Montelatto, Mariana Bonacelli [UNESP]; Villamagua-Vergara, Gabriela Carolina [UNESP]; De Brito, Carla Martins [UNESP]; Castanho, Fabiana [UNESP]; Sartori, Maria Márcia [UNESP]; De Almeida Silva, Marcelo [UNESP]; Guerra, Saulo Philipe Sebastião [UNESP] (Instituto de Pesquisa e Estudos Florestais (IPEF), 2021)
The use of biomass is increasing in the whole world, which makes it necessary to find new options for biomass production. In this scenario, bamboo appears as a potential species because of its fast-growing capacity. Hence this study aimed to obtain a mathematical model based on height (H), diameter at breast height (D) of the stem, leaf length (L) and width (W) and the number of stems per clump (N) to estimate the Bambusa vulgaris leaf area (LA) during the second year after planting. The models were obtained on a short-rotation coppice (SRC) in Botucatu, Sao Paulo, Brazil, between January 2017 and January 2018. In total, five evaluations were carried out. Before each one, a forest inventory was undertaken to select a representative clump according to the population median. From the chosen one, three culms were cut, measured, and individually defoliated. To estimate LA, 12,425 leaves L and W were measured with the assistance of a ruler; and by using a leaf area meter, the real LA was obtained. Linear and nonlinear models were tested, analyzing precision. Linear models had a higher precision when LA was correlated to L, W, H, D, and N; on the other hand, the best adjustment to the correlation between LA with C and L were the nonlinear models. Independent of the obtained model, all of them had an adjusted coefficient of determination (R2 adjusted) higher than 67%. LA variation is between 3.7 and 6.3 cm2 using these models.
Keywords: Allometric relationships; Bamboo; Biomass; Eco-physiological index; Regression models